Pitfalls in using fluorescence tagging of nanomaterials: tecto‐dendrimers in skin tissue as investigated by Cluster‐FLIM. Issue 1 (6th October 2017) - Volz, Pierre; Schilrreff, Priscila; Brodwolf, Robert; Wolff, Christopher; Stellmacher, Johannes; Balke, Jens; Morilla, Maria J.; Zoschke, Christian; Schäfer‐Korting, Monika; Alexiev, Ulrike
Abstract: Targeted topical application promises high drug concentrations in the skin and low systemic adverse effects. To locate drugs and drug‐delivery systems like nanocarriers, fluorescent dyes are commonly used as drug surrogates or nanocarrier labels in micrographs of tissue sections. Here, we investigate how labeling degree, concentration of fluorophore, and nanocarrier may affect the interpretation of these micrographs. False‐negative penetration results due to inter‐ and intramolecular quenching effects are likely. Using tecto‐dendrimers as an example, we present a detailed analysis of pitfalls in the (semi‐)quantitative evaluation of skin nanocarrier penetration. Fluorescence lifetime imaging microscopy (FLIM) allows distinguishing the target fluorescence of dye‐tagged nanocarriers from skin autofluorescence, providing a highly sensitive tool for clear‐cut localization of the nanocarriers. Cluster‐FLIM images reveal that FITC‐labeled tecto‐dendrimers penetrate the stratum corneum of human skin ex vivo and reconstructed human skin but do not cross the tight junction barrier.